Odpowiedź:
Szczegółowe wyjaśnienie:
x² - 2mx + 4 - m² = 0
I. Δ > 0
Δ = 4m² - 16 + 4m² = 8m² - 16 > 0
m² > 2
|m| > √2
I. m ∈ (-∞; -√2) ∪ (√2; +∞)
II. |x₁| + |x₂| ≤ 4 //²
x₁² + 2|x₁||x₂| + x₂² ≤ 16
x₁² + x₂² + 2|x₁x₂| ≤ 16
(x₁ + x₂)² - 2x₁x₂ + 2|x₁x₂| ≤ 16
(2m)² - 2(4-m²) + 2|4-m²| ≤ 16 (Wzory Viete'a)
2|4-m²| ≤ 16 - 4m² - 2m² + 8
2|4-m²| ≤ -6m² + 24 //:2
|4-m²| ≤ -3m² + 12
4 - m² ≤ -3m² + 12 ∧ 4 - m² ≥ 3m² - 12
2m² ≤ 8 4m² ≤ 16
m² ≤ 4 m² ≤ 4
m ∈ <-2; 2> m ∈ <-2; 2>
II. m ∈ <-2; 2>
Łącząc warunki I. i II. otrzymamy:
m ∈ <-2; -√2) ∪ (√2; 2>
Odp: m ∈ <-2; -√2) ∪ (√2; 2>.